A Theory-based Educational Pamphlet With Low-residue Diet Improves Colonoscopy Attendance and Bowel Preparation Quality. Issue 2 (February 2020) - Gausman, Valerie; Quarta, Giulio; Lee, Michelle H.; Chtourmine, Natalia; Ganotisi, Carmelita; Nanton-Gonzalez, Frances; Ng, Chui Ling; Jun, Jungwon; Perez, Leslie; Dominitz, Jason A.; Sherman, Scott E.; Poles, Michael A.; et al.
Abstract : Goals/Background: Patients who "no-show" for colonoscopy or present with poor bowel preparation waste endoscopic resources and do not receive adequate examinations for colorectal cancer (CRC) screening. Using the Health Belief Model, we modified an existing patient education pamphlet and evaluated its effect on nonattendance rates and bowel preparation quality. Study: We implemented a color patient education pamphlet to target individual perceptions about CRC and changed bowel preparation instructions to include a low-residue diet instead of the previous clear liquid diet. We compared the nonattendance rate over a 2-month period before and after the introduction of the pamphlet, allowing for a washout period during which pamphlet use was inconsistent. We compared the Boston Bowel Preparation Scale (BBPS) in 100 consecutive patients who underwent colonoscopy during each of the 2 periods. Results: Baseline characteristics between the 2 groups were similar, although patients who received the pamphlet were younger ( P =0.03). The nonattendance rate was significantly lower in patients who received the pamphlet (13% vs. 21%, P =0.01). The percentage of patients with adequate bowel preparation increased from 82% to 86% after introduction of the pamphlet, although this was not statistically significant ( P =0.44). The proportion of patients with a BBPS score of 9 was significantly higher in the pamphlet group (41% vs. 27%, P =0.03). There was no difference in adenoma and sessile serrated adenoma detection rates before and after pamphlet implementation. Conclusions: After implementing a theory-based patient education intervention with a low-residue diet, our absolute rate for colonoscopy nonattendance decreased by 8% and the proportion of patients with a BBPS score of 9 increased by 14%. The Health Belief Model appears to be a useful construct for CRC screening interventions.